Aeração intermitente em biorreatores coluna de bolhas: uma alternativa eficiente para redução do consumo de ar - Caporrino, Giancarlo Liceu (Universidade Federal de São Carlos, 2025)
This course completion work aimed to study intermittent oxygen transfer in pneumatic chemical bioreactors, through a comparative analysis with the method conventionally used for aeration of biochemical processes: the continuous regime. The aim was to verify the feasibility of replacing this method with the pulsed regime, as an efficient alternative for reducing gas consumption. For this purpose, preliminary tests were carried out under different conditions of opening and closing of the air flow control valve (decided through a central point factorial experimental design), in the water/air system, to determine important parameters in the efficiency of the process, such as the volumetric coefficient of oxygen transfer and oxygen transfer efficiency. These tests served as the basis for a statistical analysis of significance, which supported the decision to choose the conditions used (3vvm continuous and 3vvm 1F/3A) to conduct the cultures with biological beings. Then, experiments were carried out in duplicate with Saccharomyces cerevisiae yeasts in the two most promising conditions. The results demonstrated a 2% higher yield of cell growth to substrate consumption under intermittent aeration conditions. In addition, a 25% reduction in gas consumption was observed, representing significant savings in crops and contributing to the viability of the process.
Intermittent aeration in bubble column bioreactors: an efficient alternative for reducing air consumption
Keywords: Coeficiente de transferência de oxigênio; Eficiência de transferência de oxigênio; Intermitência; Aeração; SimulaFerm; Reatores pneumáticos; Coluna de bolhas; Economia; Oxigênio; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA